Manauara mothers and the education of young children : historical pluralities and resistance in the forest city = Mães manauaras e a educação das crianças pequenininhas: pluralidades históricas e resistência na cidade da floresta - Silva, Vanderlete Pereira, 1967- (2021)
Orientador: Ana Lúcia Goulart de Faria